miR-526b-3p serves as a prognostic factor and regulates the proliferation, invasion, and migration of glioma through targeting WEE1 - Wu, Ming (Cancer Manag Res, 2019)
Background: MicroRNAs play important roles in cancer progression including glioma. In this study, we aimed to explore the expression pattern, prognostic potential, and functional role of miR-526b-3p in human glioma. Materials and methods: The expression of miR-526b-3p in glioma tissues and the adjacent non-tumor tissues was determined by quantitative RT-PCR. The chi-square test was performed to evaluate the statistical associations between miR-526b-3p level and patient characteristics. The prognostic value of miR-526b-3p was analyzed by Kaplan–Meier and Cox regression analyses. The function of miR-526b-3p was analyzed by MTT, colony formation assay, transwell assay, and flow cytometry analysis in vitro. The binding between miR-526b-3p and predicted target WEE1 was verified using dual luciferase assay and Western blot analysis. Results: We found that miR-526b-3p expression was significantly downregulated in both glioma tissues and cell lines. Downregulation of miR-526b-3p was significantly associated with advanced WHO grade, lower KPS score, and inferior patient outcomes. Functional investigation indicated that overexpression of miR-526b-3p suppressed cell proliferation, migration, and invasion, and promoted apoptosis in glioma cell lines. Mechanically, WEE1 was identified as direct targets of miR-526b-3p and overexpression of WEE1 significantly suppressed the levels of WEE1. Moreover, re-introduction of WEE1 abrogates the suppression of motility and invasiveness induced by miR-526b-3p in glioma cells. Conclusion: These findings indicate that miR-526b-3p may target WEE1 and inhibit glioma tumorigenesis and progression.